IMPLIKASI PANDEMI CORONAVIRUS DISEASE 2019 (COVID-19) TERHADAP BADAN PENGAWASAN PEMILU (PEMILIHAN UMUM) PADA PILKADA (PEMILIHAN KEPALA DAERAH) SERENTAK 2020 DIPROVINSI RIAU - Endang Sri Utami; Mexsasai Indra; Maria Maya Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The current outbreak and the increasing number of Covid-19 cases inIndonesia are indeed very influential on the political sector in particular.Considering that this pandemic case is becoming more widespread, thegovernment has issued a policy regarding the postponement of the RegionalHead/Pilkada election in 2020. Indonesia has an agenda to hold a regional headelection on 23 September 2020. However, through a government regulation inlieu of Law (Perpu) Number 2 of 2020. 2020 Regarding the 3rd Amendment toLaw Number 1 of 2015 concerning the Stipulation of Government Regulations inLieu of Law Number 1 of 2014 concerning the Election of Governors, Regents,and Mayors into Law, the Government of Indonesia has decided to reschedule theelections to December 9 2020.The aim of this research is to find out the implications of the coronavirusdisease 2019 (covid-19) pandemic for the election supervisory body (generalelection) in the 2020 simultaneous local elections (regional head elections) inRiau province, by using a research methodology, namely sociological orempirical legal research, which where sociological legal research is research onlaw observing what characterizes a community's behavior in an area in an aspectof social life.The data analysis used by the researcher is qualitative data analysis,namely the analysis which does not use statistics or other things. However,researchers simply describe descriptively from the data obtained. The results ofthis study can be concluded into 3 main things. First, the inhibiting factor for theCOVID-19 pandemic on the supervision of simultaneous regional elections inRiau Province, namely when conducting surveillance during the pandemic, whenthere was an alleged violation, there was clarification via online so thatclarification was not optimal due to online, ineffective reports from the publicabout alleged violations of the candidate pair due to the system.Keywords: Simultaneous Pilkada, Bawaslu, General Election, Covid-19